عقود المزايدة (الدلالة ) وأثرها على المعاملات في الفقه الإسلامي والقانون : دراسة مقارنة - د. فرح مصطفى عبد الله (White Nile Journal for Studies and Research, 2015)
This research investigates the rules of the auction in the islamic philology and law realized in a compartive study in terms of conception. legislative evidences within the modern contemporary age The objectives of contracts signed in accordance with the various legislative rules and regulations of law The researcher studies the methods according to which auction contracts are signed and approved as well as legal allegations raised aganist auction contracts, The research is resulted in a number of signifcant results and recommendations.